Por uma história antirracista : cotidiano e vivência a partir de um estudo de caso da Escola Estadual Plácido de Castro (Diamantino/MT) - Floriano, Guilherme Eron Goulart (2024)
The dissertation addresses the importance of anti-racist education in promoting social justice in Brazil, focusing on the city of Diamantino, Mato Grosso, and the Plácido de Castro State School. Starting from the analysis of structural racism, the research examines how historical inequalities, derived from the colonial period and slavery, are still reflected in contemporary society. The first chapter explores the concept of structural racism, highlighting its manifestations and consequences for the black and indigenous population. The second chapter investigates some aspects of the local history of Diamantino, highlighting the impacts of colonization and slavery on the social and economic formation of the region. The third chapter analyzes the role of the Plácido de Castro State School as a space of resistance and construction of inclusive education, highlighting projects that value Afro-Brazilian and indigenous cultures. The dissertation concludes that anti-racist education is fundamental to deconstructing stereotypes, promoting equity and forming critical and conscious citizens, capable of contributing to a fairer and more plural society.